Urticarial Vasculitis After First Denosumab Injection in an Osteoporotic Woman Diagnosed with Cushing's Syndrome - ÖZBEK EREN, İMRE; ŞEKER, AYSUN; YAVUZ, DİLEK (My University, 2022)
Denosumab is a human-derived monoclonal immunoglobulin G2 antibody against the receptor activator of nuclear factor kappa B ligand, inhibiting the differentiation and function of osteoclast precursor cells by its antiosteoclastic action. Denosumab is approved for postmenopausal, glucocorti coid-induced, and male osteoporozis with high risk of fracture. The use of denosumab has increased in recent years. While new medications continue to be developed, the number of agents causing drug-induced vasculitis is expected to increase. It may be a good strategy to identify risk factors for vasculitis development and look for these factors before drug administration. Here, we present a rare complication of denosumab, urticarial vasculitis, after the first denosumab injection in an osteoporotic woman diagnosed with Cushing\"s syndrome.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Denosumab; osteoporosis; urticarial; vasculitis; CUTANEOUS DRUG-REACTIONS; POSTMENOPAUSAL WOMEN; BONE TURNOVER; ALENDRONATE; REDUCTION; MASS; Denosumab; osteoporosis; urticarial; vasculitis